2007
DOI: 10.1016/j.brainresrev.2007.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Pulvinar contributions to the dorsal and ventral streams of visual processing in primates

Abstract: The visual pulvinar is part of the dorsal thalamus, and in primates it is especially well developed. Recently, our understanding of how the visual pulvinar is subdivided into nuclei has greatly improved as a number of histological procedures have revealed marked architectonic differences within the pulvinar complex. At the same time, there have been unparalleled advances in understanding of how visual cortex of primates is subdivided into areas and how these areas interconnect. In addition, considerable eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
288
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(325 citation statements)
references
References 73 publications
25
288
2
2
Order By: Relevance
“…These psychophysical data from human observers with discrete pulvinar lesions lend strong support to speculations that the pulvinar plays a role in integrating fronto-parietal attentional control signals within visual processing areas (13,14,20). The patients were impaired in discriminating target features, but only when targets were accompanied by salient distracters.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…These psychophysical data from human observers with discrete pulvinar lesions lend strong support to speculations that the pulvinar plays a role in integrating fronto-parietal attentional control signals within visual processing areas (13,14,20). The patients were impaired in discriminating target features, but only when targets were accompanied by salient distracters.…”
Section: Discussionsupporting
confidence: 68%
“…Ventral pulvinar [PU(v)], conversely, which includes cell populations within inferior, lateral and medial subnuclei, exhibits reciprocal connections with successive occipitotemporal cortical areas along the ventral processing stream, and contains several topographic maps of the contralateral visual field (13,(17)(18)(19)(20). Although there are few direct connections between PU(d) and PU(v), attentional control areas such as the frontal eye fields (FEF) and lateral intraparietal area (LIP) have strong connections with the superior colliculus (SC), which subsequently projects to PU(v) (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…color, and orientation selectivity). 27 Thus, the neurogenerative changes observed in the present study may be related to glaucoma.…”
Section: Discussionmentioning
confidence: 82%
“…In simian primates, retrograde tracing experiments have shown that the tectorecipient subdivisions PIp and PIcm primarily project to cortical areas surrounding the middle temporal area (MT), which can be identified by dense myelin staining (Cusick et al 1993;Stepniewska et al 1999Stepniewska et al ,2000Kaas and Lyon 2007). Furthermore, pulvinar neurons which can be orthodromically activated from the SC are intermingled with cells that can be antidromically activated from area MT (Berman and Wurtz 2008).…”
Section: Relation To Primate Pulvinocortical Connectionsmentioning
confidence: 99%